A cascade-responsive nanoplatform with tumor cell-specific drug burst release for chemotherapy. (May 2023) - He, Xi; Xu, Bei; Fang, Aiping; Li, Xuan; Huang, Zhiying; Qin, Shugang; Xiao, Wen; Li, Guohong; Tian, Miaomiao; Fan, Na; Song, Xiangrong
Abstract: Most of the nanomedicines can reduce the side effects of anti-tumor chemical drugs but do not have good enough therapeutic efficacy, largely due to the sustained drug release profile. It might be a promising alternative strategy to develop a cascade-responsive nanoplatform against tumor with the burst release of chemotherapeutics based on the highly efficient tumor cell targeting delivery. In this work, we constructed innovative nanoparticles (PMP/WPH-NPs) consisting of two functional polymers. PMP contained the MMP-2 enzyme sensitive linker and disulfide bond, which could respond to the tumor-overexpressing enzyme MMP-2 and high-level glutathione. While WPH promoted tumor penetration and acid-responsive drug release by modifying cellular penetrating peptides and polymerizing L-histidine. PMP/WPH-NPs exhibited outstanding features including longer blood circulation time, promoted tumor-specific accumulation, enhanced tumor penetration and efficient escape from lysosomes. Subsequently, the model drug paclitaxel (PTX), widely used in the tumor chemotherapy, was encapsulated into PMP/WPH-NPs via an emulsion solvent evaporation method. Within a short period of time, PTX-PMP/WPH-NP in simulated tumor cellular microenvironment could release 8 times more PTX than that in the physiological environment, demonstrating a good potential in tumor cell-specific burst drug release. In addition, PTX-PMP/WPH-NPs exhibited stronger anti-tumor activity than PTX in vitro and in vivo, which also had good biocompatibility according to the hemolysis assay and H&E staining. In summary, our work has succeeded in designing an original polymeric nanoplatform for programmed burst drug release based on the tailored tumor targeting delivery system. This new approach would facilitate the clinical translation of more anti-tumor nanomedicines. Statement of significance: Biomaterials responsive to the tumor-specific stimulus has conventionally used in the targeted-delivery of anti-tumor drugs. However, the levels of common stimulus are not uniformly distributed and not high enough to effectively trigger drug release. In an effort to achieve a better specific drug release and promote the chemotherapeutic efficacy, we constructed a cascade responsive nanoplatform with tumor cell-specific drug burst release profile. The tailored biomaterial could overcome the bio-barriers in vivo and succeeded in the programmed burst drug release based on the tumor cell-specific delivery of chemotherapeutics. Graphical abstract: Image, graphical abstract